Impact of a bearingless machine on a shaft's rotodynamics: control of a single winding bearingless machine - Schneider, Nicolas (2020)
The aerospace industry is investigating more electrical aircraft since the early 90's. This electrification process in the aerospace industry look at replacing more and more hydraulic and mechanical actuator into electric and electromagnetic ones. The surge in electrical components in the aircraft leads to an increase in electric power consumption. For this reason there is a growing interest into the design of generator for aero-engines. Generator for turbofan are usually attached via a gear box to the high pressure shaft of the turbine. But in the last 20 years, several studies have tried to use electrical generators directly in-line with the turbine's shaft. This raised some challenges in terms of electrical machine performance, heat management as well as finding the good typologies to use for such a task.